The purpose of whisper networks: a new lens for studying informal communication channels in organizations - Johnson, Carrie Ann (Frontiers in Communication, 2023)
This paper explores whisper networks, which are informal communication networks women use to share information about sexual harassment and sexual harassers in the workplace. Women use whisper networks to share information about people known for sexual harassment or assault. This study offers an innovative approach to studying the nuances and dynamics of sexual harassment and communication in the workplace by focusing on women’s experiences in whisper networks. To examine these backchannels, I conducted 20 semi-structured interviews with participants who participated in whisper networks in their organizations. Using grounded theory and thematic analysis, I established three emergent theories about the purposes whisper networks serve in organizations. Whisper networks 1) serve as protection in organizational cultures of harassment and 2) help women make sense of their harassment experience through sensemaking. Whisper networks also serve the purpose of 3) identifying harassers because harassers are not readily apparent when entering a new work situation. These findings establish a baseline of theories to explain the purposes whisper networks serve and have theoretical and practical implications for future research on sexual harassment, whisper networks, and informal communication networks.